Public Attitudes and Interests in Using Online Transactions (TAM Application And TRA Model) - Rastini, Ni Made; Respati, Ni Nyoman Rsi (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
This study aims to investigate the public's interest in using online transactions, especially mobile by Technology Acceptance Model (TAM) and Theory of Reasoned Action (TRA). The sample in this study was 200 people. The data analysis technique in this study used Partial Least Square (PLS). The results showed that the perceived ease of use and perceived usefulness had a positive and significant effect on user attitudes. Subjective norm variables, user attitudes have a positive and significant impact on individual behavior interest, perceived ease of use has a positive and significant effect on the perceived usefulness. This research suggests that the banking sector is expected to add features to make it easier and provide more benefits for their customers in using mobile banking.